(untitled) (International Journal of Environmental Sciences, 2025)
The study currently discussed offers a detailed green and sustainable method or scheme for larger scale production of zinc oxidant, 225124e (ZnO) nanoparticles through Epipremnum aureum extract a medicinal plant known for high bioactive phytochemical contents. This green alternative caters to the tenets of green chemistry by not using toxic chemical reducing agents thereby preventing hazards and the cost in the process is minimal. The plant extract was prepared by Soxhlet extraction and was tested for pharmacogenetic and phytochemical screening that certified the plant extract of the key constituents such as alkaloids, flavonoids, tannins, and saponins that has natural reducing and capping properties. ZnO NPs were synthesized with the different extract–to–precursor ratios (F1–F7) and characterized using UV-Vis’s spectrophotometry, FTIR, XRD, TEM, and DLS. The nanoparticles had the form of spheres, hexagonal wurtzite structure, and high entrapment efficiency. Biological aspects of the produced ZnO nanoparticles were studied using antimicrobial tests versus Escherichia coli and Staphylococcus aureus using the DPPH radial scavenging method as an indicator of antioxidant activity. There were evident signs of high antibacterial zones of inhibition and dose-dependent antioxidant actions. Furthermore, the environmental application was evaluated with the help of the photocatalytic degradation of methylene blue dye with the influence of UV light, where a high degree of degradation and reusability was detected. In general, the results predict the initiation of stable, bioactive ZnO nanoparticles by using Epipremnum aureum. The fact that paddocked viruses continue to persist despite the availability of active and effective vaccines against many is a strong indication. There is clearly fundamental research that is quite critical in nature and that is payoffs, and good feelings have yet to be seen.